Intelligentsia and Opposition — the Modern Meaning of S. N. Bulgakov’s Article “Heroism and Ascension (From Reflections on the Religious Ideals of the Russian Intelligentsia)” - V. B. Aleksandrov (Управленческое консультирование)
The article examines the views of the Russian philosopher S. N. Bulgakov on the role of the intelligentsia in the revolution of 1905–1907. He draws attention to his understanding of the worldview of the political activity of the intelligentsia, as which he sees its “self-disposition.” It is shown that the natural support of the intelligentsia in the revolution, according to S. N. Bulgakov, is youth, due to emotional immaturity and a low level of education. The special importance of contrasting the “heroism” of the intelligentsia with the spirit of ascension, characteristic of Christian saints and involving intense everyday work, based on humility as the most important worldview prerequisite for ascension, is emphasized. It is noted that with the obvious similarity in the activities of modern opposition to the revolutionary impulse of the intelligentsia of the early twentieth century, there are also fundamental differences. They are related to mismatch of target settings. If the Russian intelligentsia of the beginning of the century aimed at a fundamental change in the social system, then the modern creative class is driven by the desire to destroy the existing power, due to the quite practical interests of personal success.